2014
DOI: 10.1590/1980-4415v28n48a19
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry and rotation skills of prospective elementary mathematics teachers

Abstract: The aim of this study was to investigate the skills and deficiencies of senior university students enrolled in a mathematics education program with the concepts of symmetry and rotation of geometric figures. The study was conducted with 32 prospective teachers in the Department of Education at a public university located in Western Turkey. This descriptive study was designed with a case study. A structured interview technique was used for data collection. A measurement tool consisting of 12 drawing problems te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Thus, such an understanding may have led the participants to think shapes as a whole. The study by Turgut, Yenilmez & Anapa (2014) concluded that the prospective teachers had difficulty in finding the axis of symmetry and determining whether the given two objects are symmetrical or not. It may be argued that the prospective teachers in this study experienced some similar difficulties and fell into misconception.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…Thus, such an understanding may have led the participants to think shapes as a whole. The study by Turgut, Yenilmez & Anapa (2014) concluded that the prospective teachers had difficulty in finding the axis of symmetry and determining whether the given two objects are symmetrical or not. It may be argued that the prospective teachers in this study experienced some similar difficulties and fell into misconception.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…The results of the study support the idea of this research by saying that the symmetrical structures can be used to develop the skills in lower grades. Finally, Turgut, Yenilmez and Anapa, (2014) found that 32 pre-service Turkish elementary mathematics teachers can determine the symmetry axis when a rotation axis was provided but failed in case of absence of an axis.…”
Section: Discussionmentioning
confidence: 99%
“…Alanyazında sadece öğrencilerin değil öğretmen ve öğretmen adaylarının dönüşümler konusunda bilgi düzeylerinin yetersiz olduğunu belirten çalışmalar da (Ada & Kurtuluş, 2010;Al-Khateeb, 2016;Aktaş & Ünlü, 2017;Desmond, 1997;Gürbüz & Durmuş, 2009;Hacısalihoğlu-Karadeniz, Baran, Bozkuş & Gündüz, 2015;Harper, 2002;Kambilombilo & Sakala, 2015;Law, 1991;Mbusi, 2016;Son, 2006;Turgut, Yenilmez & Anapa, 2014) -Dönmede şekil üzerindeki her bir noktanın bir nokta etrafında belirli bir açıyla saat veya tersi yönünde dönüşüme tabi olduğunu ve şekil ile görüntüsünün eş olduğunu keşfeder.…”
Section: Introductionunclassified